Влияние параметров якоря линейного импульсного электромеханического преобразователя на его эффективность - Болюх, В.Ф.; Кочерга, А.И.; Щукин, И.С. (Електротехніка і електромеханіка, 2017)
Разработана математическая модель линейного импульсного электромеханического преобразователя (ЛИЭП), описывающая быстропротекающие и взаимосвязанные электромагнитные и электромеханические процессы, проявляющиеся при перемещении якоря относительно индуктора. Показано, что при увеличении высоты электропроводящего, катушечного и ферромагнитного якорей ЛИЭП происходит увеличение импульса силы. Наибольшая скорость развивается в ЛИЭП с катушечным якорем, а наименьшая – в ЛИЭП с электропроводящим якорем. В ЛИЭП с катушечным и ферромагнитным якорями реализуются практически одинаковые значения импульса электродинамической и электромагнитной силы, а в ЛИЭП с электропроводящим якорем импульс электродинамической силы в 1,52 раза меньше. Введен интегральный показатель эффективности, который в относительном виде учитывает силовые, скоростные, энергетические, электрические и полевые показатели. Установлено, что при всех стратегиях оценки эффективности наиболее эффективным является ЛИЭП с катушечным якорем, а наименее эффективным является ЛИЭП с ферромагнитным якорем. Б Розроблена математична модель лінійного імпульсного електромеханічного перетворювача (ЛІЕП), яка описує швидкісні та взаємопов’язані електромагнітні та електромеханічні процеси, що проявляються при переміщенні якоря відносно індуктора. Показано, що при збільшенні висоти електропровідного, котушкового та феромагнітного якорів ЛІЕП відбувається збільшення імпульсу сили. Найбільша швидкість розвивається в ЛІЕП с котушковим якорем, а найменша – в ЛІЕП з електропровідним якорем. В ЛІЕП з котушковим та феромагнітним якорями реалізуються практично однакові значення імпульсу електродинамічної та електромагнітної сили, а в ЛІЕП з електропровідним якорем імпульс електродинамічної сили у 1,52 рази менший. Запропонований інтегральний показник ефективності, який у відносному вигляді враховує силові, швидкісні, енергетичні, електричні та польові показники. Визначено, що при усіх стратегіях оцінювання ефективності найбільш ефективним є ЛІЕП с котушковим якорем, а найменш ефективним є ЛІЕП з феромагнітним якорем. Purpose. The evaluation of the effect of armature parameters on the efficiency of a linear pulsed electromechanical converter, taking into account the power, speed, constructive and environmental parameters. Methodology. First, the height of the electrically conductive, coil and ferromagnetic armature of a linear pulse electromechanical converter is determined, at which the highest velocity develops. An integral efficiency index is introduced, which takes into account, in a relative way, the power, speed, energy, electrical and field characteristics of the converter. Variants of the efficiency evaluation strategy are used that take into account the priority of each indicator of a linear pulse electromechanical converter using the appropriate weighting factor in the integral efficiency index. Results. A mathematical model of a linear pulsed electromechanical converter is developed. It is established that as the height of the electroconductive, coil and ferromagnetic armature increases, the force pulse increases. The greatest speed develops with the use of a coil armature, and the smallest with an electroconductive armature. In the converter with coil and ferromagnetic armature, practically the same values of the electrodynamic and electromagnetic force pulse are realized, while in the converter the electrodynamic force is 1.52 times smaller in the converter by the electrically conductive armature. It is established that with all efficiency evaluation strategies, the converter with a coil armature is the most effective, even in spite of its constructive complexity, and the converter with a ferromagnetic armature is the least effective, although it is constructively the simplest. Originality. For the first time, using the integral efficiency index, which takes into account the power, speed, energy, electrical and field indices in a relative way, it is established that with all efficiency evaluation strategies, the converter with a coil armature is the most effective, and the converter with a ferromagnetic anchor is the least effective. Practical value. The height of the electrically conductive, coil and ferromagnetic armature of a linear pulse electromechanical converter is determined, at which the highest speed develops. It is shown that when using an electrically conductive armature, the value of the electrodynamic force pulse is lower than when using a coil and ferromagnetic armature. It is established that the converter with a coil armature is the most efficient, and the converter with a ferromagnetic armature is the least effective.